Exploring the Emotional Impact of Contrasting Melodies and Lyrics: A Quasi-Experimental Study on Mood Alteration - Fitriani, Arbania; Suryani, Andi; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2024)
The phenomenon of emotional incongruence in Dangdut Koplo, where cheerful melodies are paired with sorrowful lyrics, creates a unique cognitive dissonance that challenges listeners' emotional processing. This juxtaposition is prominent in Didi Kempot's works, blending lively rhythms with melancholic themes of heartbreak and longing. Such contrasting elements evoke strong emotional responses, making the genre a compelling subject for psychological exploration. This study pioneers exploring emotional incongruence in Dangdut Koplo, aiming to replicate and expand upon Stratton and Zalanowski’s findings. Using a quasi-experimental design, 55 psychology students were assessed with PANAS before and after listening to four songs by Didi Kempot. Results revealed a significant increase in Negative Affect (NA) post-exposure, while Positive Affect (PA) remained stable. Regression analysis demonstrated lyrical content had a stronger impact than melody on mood shifts. Participants who related to the lyrics experienced more pronounced negative emotions. Age and gender significantly influenced reactions, highlighting personal and cultural factors. This study provides insights into music's psychological mechanisms and implications for music therapy across diverse cultural contexts.